Pemasaran Skincare Di Indonesia: Sebuah Fenomena Budaya Populer Korea Selatan - Muhammad Iqbal Revilliano Trisandri; Silmi Aulia Alkautsar; Mohamad Zein Saleh (Jurnal Manajemen Riset Inovasi, 2024)
The rise of the Korean Wave which is currently popular in Indonesia, especially among the younger generation, also has an impact on the millennial generation. Without realizing it, the younger generation in Indonesia presents Korean culture which is spread through K-Pop and K-sensation such as beauty products (beauty and skin health care products). Most young people who love K-Pop have their own Korean names. This name appears on their casual network and many mention "Korea" or "Seoul" as their starting place. (Valenciana & Pudjibudojo, 2022).